2006
DOI: 10.1016/j.jacc.2005.09.043
|View full text |Cite
|
Sign up to set email alerts
|

An Implantable Loop Recorder Study of Highly Symptomatic Vasovagal Patients

Abstract: In highly symptomatic patients with VVS, the heart rhythm observed during spontaneous syncope does not correlate with the HUT. The heart rhythm during the first spontaneous syncope is identical to the recurrent syncope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
3
3

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(14 citation statements)
references
References 28 publications
3
9
1
1
Order By: Relevance
“…Similar ECG features have been occasionally described in individual patients in clinical studies (9,11,12) and in a few case reports (13)(14)(15)(16); no follow-up is reported.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Similar ECG features have been occasionally described in individual patients in clinical studies (9,11,12) and in a few case reports (13)(14)(15)(16); no follow-up is reported.…”
Section: Discussionsupporting
confidence: 75%
“…The adenosine test appeared to be sensitive enough to identify the patients with idiopathic AV block in this study, but it showed a very low specificity in other studies in which there was a lack of correlation between the responses to the test and the mechanism of spontaneous syncope documented by implantable loop recorder (11,12). There is not a clear-cut cutoff of APL value between idiopathic AV block patients and normal control subjects.…”
Section: Discussioncontrasting
confidence: 61%
“…The ECG of the ATP-sensitive patients showed the same characteristics of idiopathic AV block described above. Similar ECG features have been occasionally described in individual patients in clinical studies 13 and in few case reports. [14][15][16][17] The original description 1 included 18 cases.…”
Section: Epidemiology Of Syncope Due Idiopathic Av Blocksupporting
confidence: 79%
“…Deharo et al showed that the heart rhythm observed during spontaneous syncope in vasovagal patients with ILRs does not correlate with head-up tilt test 28. Garcia-Civera et al demonstrated that a negative electrophysiological study and head-up tilt test is of little value to predict the mechanism of syncope 29.…”
Section: Discussionmentioning
confidence: 99%